The Relationship between Smoking Behavior and the Incidence of Tuberculosis at the Medan Sunggal Public Health Center - Andre Christian Ginting; Andrico Napolin Lumbantobing (HM Publisher, 2021)
Tuberculosis is an infectious disease caused by bacteria in the form of rods (bacilli) known as Mycobacterium tuberculosis. This disease is included as a chronic infectious disease. The causes of the increase in TB cases each year are still various. One of them is smoking behavior. A person who smokes will have twice the risk of contracting TB. This study aims to determine the relationship between smoking behavior and the incidence of pulmonary tuberculosis in the work area of the Medan Sunggal Puskesmas in 2019. This study is an analytical study with a cross sectional design. The population of this study were patients with pulmonary TB in the work area of the Medan Sunggal Public Health Center in 2019. The sample size used was 104 people who had met the inclusion and exclusion criteria. In the second study, the data collection tool was through the Puskesmas medical records. Data analysis was performed using the statistical test is chi square. the result showed that there was a relationship between smoking behavior and the incidence of pulmonary tuberculosis in Medan Sunggal Public Health Center with an OR (95% CI) value of 105,125 (13,280-832,161), which means that respondents who smoke will have 105,125 times the risk of suffering from pulmonary tuberculosis compared to non-smoking respondents. From the results of 95% CI, it can be seen that the lower limit and upper limit values (CI values) not include 1.00, so the results of the study are statistically significant at the value of α = 0.001. Smoking behavior has an insignificant relationship with the incidence of pulmonary tuberculosis at Medan Sunggal Puskesmas in 2019. It is recommended that the primary care should provide support and sources of information about smoking habits, especially for patients who have been diagnosed with pulmonary TB.